Upaya Meningkatkan Hasil Belajar Siswa Menggunakan Media Pembelajaran Audio Visual Materi Ilmu Pengetahuan Alam - Turisia, Ria Franciska (Al-Miskawaih: Journal of Science Education, 2022)
Learning outcomes and interest in learning are causal in the learning process, with increasing student interest in learning it will provide motivation and enthusiasm for learning so that students can focus and ultimately maximize student learning outcomes. The concrete step that can be taken is to apply learning media in the teaching and learning process. The purpose of this study was to determine whether the application of science learning media could improve the learning outcomes of 7th grade students of SMPN 11 Jambi City. This research was carried out in three cycles, namely Cycle I, II and III. For each cycle, different actions are taken by correcting the weaknesses contained in the next cycle. Based on the results of the study, the results of the evaluation that have been carried out have increased learning outcomes with an average value of 6.0 in the first cycle, the average value increased to 7.8 in the second cycle and increased again the average value to 8.5 in the first cycle. III. Thus, it can be seen that learning increases in each cycle. Based on the results of the study, it can be concluded that through the application of audio-visual learning media in science material, it can improve the learning outcomes of 7th grade students of SMPN 11 Jambi City. Hasil belajar dan minat belajar merupakan sebab akibat dalam proses pembelajaran, dengan peningkatan minat belajar siswa akan memberikan motivasi dan semangat belajar sehingga siswa dapat fokus dan akhirnya akan memaksimalkan hasil belajar siswa. Langkah kongkrit yang dapat dilakukan adalah menerapkan media pembelajaran dalam proses belajar mengajar. Tujuan dari penelitian ini adalah untuk mengetahui apakah penerapan media pembelajaran IPA dapat meningkatkan hasil belajar siswa kelas 7 SMPN 11 Kota Jambi. Penelitian ini dilaksanakan tiga siklus, yaitu Siklus I, II dan III. Untuk setiap siklus dilakukan tindakan yang berbeda dengan memperbaiki kelemahan-kelemahan yang terdapat pada siklus berikutnya. Berdasarkan hasil penelitian menunjukkan hasil evaluasi yang telah dilakukan terjadi peningkatan hasil belajar dengan nilai rata-rata 6,0 pada siklus I, meningkat nilai rata-rata menjadi 7,8 pada siklus II dan meningkat kembali nilai rata-rata menjadi 8,5 pada siklus III. Dengan demikian dapat diketahui pembelajaran meningkat disetiap siklus. Berdasarkan hasil penelitian dapat disimpulkan bahwa melalui penerapan media pembelajaran audio visual pada materi IPA dapat meningkatkan hasil belajar siswa kelas 7 SMPN 11 Kota Jambi.